Heterogeneous responses of systolic and diastolic left ventricular function to exercise in patients with heart failure and preserved ejection fraction. (10th August 2015) - Kasner, Mario; Sinning, David; Lober, Jil; Post, Heiner; Fraser, Alan G.; Pieske, Burkert; Burkhoff, Daniel; Tschöpe, Carsten
Abstract: Aims: This study aimed to evaluate ventricular diastolic properties using three‐dimensional echocardiography and tissue Doppler imaging at rest and during exercise in heart failure with preserved ejection fraction (HFpEF) patients with borderline evidence of diastolic dysfunction at rest. Methods and results: Results obtained from 52 HFpEF patients (left ventricular ejection fraction ≥ 50%) identified on the basis of heart failure symptoms and E / E ′ values between 8 and 15 were compared with those obtained in 26 control patients with no evidence of cardiovascular disease. Mitral flow patterns, tissue Doppler imaging, and volume analysis obtained by three‐dimensional echocardiography were performed at rest and during bicycle exercise. Diastolic compliance was indexed by the E / E ′ ratio and left ventricular end‐diastolic volume [( E / E ′)/EDV]. There were no significant differences in end‐diastolic volume (EDV), stroke volume (SV), or ejection fraction at rest between groups. In 27 of the 52 patients, E / E ′ increased during exercise (11.2 ± 3.7 to 16.8 ± 10.5), driven by a failure to augment early diastole ( E ′). This correlated with a fall in SV and was associated with an increase in the diastolic index ( E / E ′)/EDV as a measure for LV stiffness (0.122 ± 0.038 to 0.217 ± 0.14/mL), indicating that impaired diastolic reserve (designated PEF‐ID R) contributed to exercise intolerance. Of the 52 patients, 25 showed no changes in E / E ′ during exercise associated with a significant rise in SV and cardiac output, still inappropriate compared with controls. Despite disturbed early diastole ( E ′), a blunted increase in estimated systolic LV elastance indicated that impaired systolic reserve and chronotropic incompetence rather than primarily diastolic disturbances contributed to exercise intolerance in this group (designated PEF). Conclusion: Three‐dimensional stress echocardiography may allow non‐invasive analysis of changes in cardiac output that can differentiate HFpEF patients with an inappropriate increase or a fall in SV during exercise. Impaired systolic or diastolic reserve can contribute to these haemodynamic abnormalities, which may arise from different underlying pathophysiologic mechanisms.